Microperforation prolotherapy: a novel method for successful nonsurgical treatment of atraumatic spontaneous anterior sternoclavicular subluxation, with an illustrative case - Stein A; McAleer S; Hinz M (Dove Medical Press, 2011)
Alvin Stein1, Scott McAleer2, Marty Hinz31Stein Orthopedic Associates, PA, Plantation, FL, USA; 2University of Central Florida, Orlando, FL, USA; 3Clinical Research, Neuroresearch Clinics, Inc, Cape Coral, FL, USABackground: Surgical repair of an atraumatic spontaneous anterior subluxation of the sternoclavicular joint (herein referred to as the “SCJ”) is often associated with poor outcome expectations. With traditional treatment, successful conservative therapy usually incorporates major lifestyle alterations. This manuscript discusses a novel approach known as “microperforation prolotherapy”. To illustrate the technique, the care of a patient who benefitted from this treatment is reviewed.Purpose: To present a novel form of treatment with an illustrative case that demonstrates the potential efficacy of microperforation prolotherapy of the SCJ.Patient and methods: A novel approach to treatment of bilateral subluxation of the sternoclavicular joint with microperforation prolotherapy is discussed. The clinical course of a 21-year-old male with bilateral subluxation of the SCJ, which seriously hampered the patient's athletic and daily living activities, is used as a backdrop to the discussion.Results: Following microperforation prolotherapy, the instability of the SCJ was replaced by full stability, complete range of motion, and the opportunity to engage in all of the athletic endeavors previously pursued. There is no scar or other cosmetic defect resulting from the treatment received.Conclusion: Anterior sternoclavicular joint subluxation has a poor record of complete recovery with surgical procedures or conservative measures with regard to providing restoration of full lifestyle function. This manuscript documents a novel microperforation prolotherapy treatment that induced healing and restored full stability to the ligament structures responsible for the condition in a completely safe and effective fashion, allowing the patient to resume full lifestyle activities without restriction. The exceptional response to treatment noted here is encouragement for further studies.Keywords: sternoclavicular joint subluxation, shoulder pain, sternoclavicular instability, spontaneous instability, anterior subluxation